SISTEM INFORMASI KREDIT SAHABAT PADA BADAN USAHA MILIK DESA (BUMDES) DESA SEMAMUNG BERBASIS WEB - Rodianto; Jundi Khoirullah; Yana Karisma (Jurnal Informatika Teknologi dan Sains, 2020)
One of the efforts the acceleration of the economy of the village is the availability of venture capital. Each village has a business entity that is named the village owned enterprises (BUMDes). A business entity has one work program, namely "credit Companions (KRABAT)" which provides capital for the community. This is done in order to realize the program villages without the moneylenders. By applying the appropriate information technology can help improve effectiveness in a given job. Credit information system's best friend On the villageowned enterprise (Bumdes) of this Web-based Semamung will be built using the PHP programming language, software development using a waterfall, a MySQL database, and Sublimetext. This system can be used to facilitate the management of the village's best friend BUMDes Semamung in the process of recording data and search communities that do the borrowing either from the loan amount submitted as well as the rest of the loans have been paid and good storage of the amount deposited or taken from the village of Semamung in the companion of BUMDes-scale storage. This system can make the officer in carrying out the process of filing a loan or credit, savings, and installment Credit process in BUMDes village of Semamung best friend because it uses a computerized system. Thus the process of logging and counting KRABAT on BUMDes village of Semamung can be carried out effectively because of logging and counting process were no longer recorded manually.